Rutting resistance of SMA mixtures incorporating crumb rubber / Herda Yati Katman - Herda Yati, Katman (2016)
With the exponential growth in the number of automobiles in Malaysia in recent years, the problem generated by waste tyres has also increased. Therefore, incorporating waste tyres as an additive in road pavement might be an option to overcome the increase in the number of waste tyres as well as address some of the pavement problems, such as rutting deformation. Crumb rubber modified binder is acknowledged to provide better rutting resistance. Many research works have been implemented on the effects of chemical additives to further increase the performance of crumb rubber modified binders. Recent studies have shown that the properties of crumb rubber modified binders can be improved by adding crosslinking agents, such as trans-polyoctenamer (TOR) for which the main function is to activate the rubber-bitumen interaction and improve crosslinking. This study was conducted to determine a method to improve the rutting resistance of SMA 20 bituminous mixtures. Accordingly, different percentages of crumb rubber were added to bitumen using different blending methods (continuous blend and terminal blend) in order to produce different concentrations of crumb rubber modified binder. In addition, a crosslinking agent, namely, trans-polyoctenamer (TOR), was introduced in the crumb rubber modified binder with the intention of further improving the binder properties and minimizing the rutting problem. In order to analyse the performance of the binders and mixtures as well as to evaluate the relationship of the rutting characteristics between them, a series of binder tests and bituminous mixture tests were performed. In the final analysis, the author found that the binder tests were not adequate to evaluate the rutting characteristics of bituminous mixtures. For instance, in the case of the crumb rubber modified binder prepared using the terminal blend method, most of the binder tests show that the terminal blend binder displays the best performance; however, in respect of the bituminous mixtures it became worse. To further study the creep behaviour (rutting characteristics) of bituminous mixtures, the dynamic creep test was performed using the universal testing machine (UTM) at different temperatures and stress levels. Finally, the creep behaviour of the specimens was estimated using the Zhou three-stage creep model. The results show that crumb rubber and TOR significantly affected the rutting parameters, especially at high stress levels and temperatures. Moreover, based on the Zhou model, it was concluded that resistance to permanent deformation (rutting resistance) was improved by the application of crumb rubber and TOR. In addition, multiple linear regression (stepwise method) was used for statistical analysis for which the main objective was to develop an equation (regression model) that could be used for predicting the rutting of the mixtures for all factors engaged. A secondary purpose was to use regression analysis as a means of explaining the causal relationship among the factors (significant level).